Analisis Pemanfaatan Media Promosi Dalam Pemasaran Dana Tabungan IB Hijrah Haji di PT. Bank Muamalat Indonesia,Tbk. KCP. Rantauprapat - Jahara, Afrilia; Rokan, Mustafa Khamal (Universitas Labuhanbatu, 2021)
This study intends to break down the utilization of limited time media in showcasing IB Hijrah Haji reserve funds items at PT. Bank Muamalat Indonesia, Tbk. KCP. Rantauprapat. The plan of the issue in this study is the manner by which the media advancement by PT. Bank Muamalat Indonesia, Tbk. KCP. Rantauprapat in promoting IB Hijrah Haji investment funds items? How is the Progression of Enrollment for IB Hijrah Haji investment funds items at Bank Muamalat Indonesia, Tbk. KCP. Rantauprapat?. The techniqu utilized in this examination is the clear strategy. Information assortment procedures utilizing interview strategies, perception and documentation The information investigation method utilized distinct subjective. The aftereffects of this study show that the Media Advancement directe by Bank Muamalat Indonesia, Tbk. KCP. Rantauprapat is Publicizing medi utilizing print media, Exposure Advancement Media (Exposure) by going t local area exercises like going to recitations/Perwiritan and visitin schools, Individual Selling Media (Individual Selling) by visiting individuals' homes or planned clients.